MENGHITUNG PENCARIAN RUTE TERDEKAT PADA OBJEK WISATA MENGGUNAKAN ALGORITMA A-STAR ( STUDI KASUS : KECAMATAN NYALINDUNG - Sariyanti Sariyanti (STMIK KAPUTAMA, 2020)
The search for the shortest path becomes a tourist attraction that is in great demand by tourists who have never visited a tourist attraction in Nyalindung District. At this time information about tourism has spread on the internet but no one has made a special article about the shortest path to travel in Nyalindung District.Therefore, the authors make a special case study of the search for the closest route to attractions in the district of Nyalindung. The goal is to find an alternative route with the shortest search path from the initial location to the final location. This study uses qualitative, data collection based on Google Maps and direct monitoring. To solve the problem of finding the shortest path using the A-Star Algorithm. The A-Star algorithm is used to find the shortest path of two paths (alternative routes). The shortest path search results use the A-Star Algorithm to make it easier for tourists and find find tourist locations by saving search time.Keywords: A-Star Algorithm, Google Maps, Shortest Path, Travel, heuristik